Students’ Perception on Online Learning At Mega Buana University - Tri Endar Yogi Setiadi Saputra; Syachrir Syamsuddin (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Students' Perception on Online Learning at Mega Buana University. The objective of this research is to find out the students’ perception about online learning at Mega Buana University. The researcher was the key instrument. The samplings of data sources were done purposively. The research technique was triangulation (combined), data analysis was quantitative. The result of this research based on the percentage of their answers that can be seen from the table, many answers very agree and agree than less agree and disagree. It means that can be said that their perception about online learning is good system and process for them.